Molecular detection of Escherchia coli carrying uropathogenic-specific-protein and typeâ…¢ secretion system from patients with urinary tract infection - A. Jawad, Alaa; N. Ayyez, Hayder; Al-Rammahi, Miran (Al-Qadisiyah Journal of Pure Science, 2018)
To specify Escherichia coli, infects urinary bladder, whether it is a urospecific bacterium or not, this polymerase-chain-reaction (PCR)-based study was performed. Urine specimens from patients with urinary tract infection were subjected to a process of bacterial recovering 20 isolates of E. coli. The isolates were then used for PCR-based identification of uropathogenic specific protein (usp) and type III secretion system ( ETTT) genes. The results revealed the presence of usp in 6 (30%) isolates and ETTT in 2 (10%) isolates. So these results give no-doubt confirmation that these isolates of E. coli are urospecific and pathogenic bacteria.